Pulmonary Function Changes in Carcinoma Breast Patients Treated with hypo-fractionated Radiotherapy - Sharma, Divya; Khandelwal, Mayur; Sharma, Neeti; Jakhar, Shankar Lal (Asian Pacific Journal of Cancer Care, 2025)
Background: Radiation treatment in breast cancer has very pivot role. Post operative chest irradiation in carcinoma breast is necessary because it prevents recurrence. By radiation treatment survival increase but also it increases local toxicity. This study intends to assess the acute and late pulmonary in patients undergoing post-operative radiation with hypo-fractionated radiotherapy techniques. Material and methods: A total of 40 female patients of breast cancer, treated by mastectomy, were taken in our study from January 2022 to July 2022 after having obtained informed consent. All patients had PFT`s before the start of RT and post RT at 3 months, 6 months and after 2 years to assess early and late side effects. Results: Results shows that we can use hypo-fractionated regimes as no significant long-term toxicity found in our study. Conclusion: Our study has shown that hypo-fractionated regimes are not detrimental to the effective and safe delivery of radiation post- mastectomy in breast cancer patients especially when concerning acute or late pulmonary damage, with data in this study revealing no clinically statistically significant acute or late pulmonary toxicity even at a follow up of 2 years.